Measuring Customer Experience in Select Rural Banks Through SERVQUAL - Nelda A. Rosima; Elaine Joy C. Apat (International Journal of Academe and Industry Research, 2022)
Improvement of every financial institution is based on the quality of service they provide. In the Philippines, most bank’s clients prefer financial institutions that render quality service. With resurgence of interest and need for effective delivery of service, this study aimed to determine the effectiveness of service provided by selected rural banks in terms of tangibility, responsiveness, reliability, empathy and assurance. It utilized descriptive method and selected two hundred client-respondents through quota sampling. The results showed significant differences in empathy, reliability, responsiveness and assurance when grouped according to sex, kind of service availed and monthly income. However, no significant difference was found when the five dimensions are grouped according to age and civil status. The results further revealed that the company is highly effective in providing quality service in terms of assurance and reliability, and effective in terms of tangibility, responsiveness, and empathy. From the assessments of customer experience, the banks need to provide more modernized facilities for better services, furnish more pamphlets and promotional tools to educate clients on the bank regulations, new products or services catered, and improve facilities by providing additional seats and reading materials while clients are waiting for their transactions.